Impact of aluminosilicates on productivity, carcass traits, meat quality, and jejunum morphology of broiler chickens - Mirosław Banaszak (Poultry Science, 2020)
The aim of the study was to compare production results and quality of meat, as well as histological features of the jejunum in broiler chickens administered feed with 1% addition of zeolite or halloysite, with the addition of aluminosilicates to litter (4.50 kg/m2) throughout the rearing. In the experiment, 300 male broilers were used for 6 wk. They were divided into 3 groups, each of 10 repetitions (10 birds each). Group 1 was a control, halloysite was added to feed and litter in group 2, while zeolite was applied instead of halloysite in group 3. After rearing, 10 selected birds from each group were slaughtered. Selected production properties and degree of footpad dermatitis were examined, and histomorphometric examination of the jejunum was performed. The lowest yield and the highest proportion of neck with skin in the carcass were demonstrated in group 2 (P < 0.05). The lowest percentage of skin with subcutaneous fat was found in group 3 (P < 0.05). A decrease in lightness (L∗) and yellowness (b∗) was demonstrated in group 2, while redness (a∗) was the lowest in group 3 (P < 0.05). Group 2 was characterized by the lowest water-holding capacity in breast muscles, and in group 3, in leg muscles (P < 0.05). In group 3, the highest fat content and the lowest water content in the breast muscles (P < 0.05) were found. The leg muscles in groups 2 and 3 were characterized by the highest a∗, and in group 2, by b∗. The control group had the lowest protein and the highest fat content in leg muscles. In the intestine from group 2, a higher height (P < 0.05) and surface area (P < 0.01) of intestinal villi were found, in comparison to group 3. The width of intestinal villi was higher in groups 2 and 1 than in group 3 (P < 0.05), similarly the depth of intestinal crypts. The addition of zeolite could be proposed because of the obtained production results, while the halloysite had a positive effect on the histomorphometric features of the jejunum.